Lipid-mRNA nanoparticles landscape for cancer therapy - Li, Yin; Fang, Hengtong; Zhang, Tao; Wang, Yu; Qi, Tingting; Li, Bai; Jiao, Huping (Frontiers in Bioengineering and Biotechnology, 2022)
Intracellular delivery of message RNA (mRNA) technique has ushered in a hopeful era with the successive authorization of two mRNA vaccines for the Coronavirus disease-19 (COVID-19) pandemic, and a wide range of clinical studies are proceeding or may be initiated in the foreseeable future to treat and prevent a lot of diseases including metabolism disease and cancers. However, efficient and non-toxic delivery of therapeutic mRNAs maintains the key limited step for their widespread applications in human beings. mRNA delivery systems are in urgent demand to resolve this difficulty. Recently lipid nanoparticles (LNPs) vehicles have prospered as powerful mRNA delivery tools, enabling its potential applications in malignant tumors via cancer immunotherapy and CRISPR/Cas9-based gene editing technique. This review discusses formulation components of mRNA-LNP, summarizes the latest findings of mRNA cancer therapy, highlights challenges, and offers directions for more effective nanotherapeutics for cancer patients.